2009
DOI: 10.4067/s0716-10182009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriemia por Vibrio parahaemolyticus: Reporte de caso y revisión de la literatura

Abstract: Vibrio parahaemolyticus is a facultative anaerobic gram negative rod responsible of sea food-associated diarrhoea. Although less common, it also causes wound infections and bacteraemia. We present a case of bacteraemia by this agent and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…These variance reports might be associated with the region or environmental activities in their individual isolation sites or the flexible and changing nature of V. cholerae in diverse environment [ 64 ]. In the reports of Guevara et al [ 65 ], resistance was not observed amongst the Vibrio strains but the trend changed over time as subsequent simultaneous report between 1992 and 2017 shows that [ 59 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] V. cholerae is emerging in resistant profile and multiple antibiotic resistance which have also extended from penicillanases or β-lactamases of various class to carbapenemases as affirmed during their study. This is further affirmed in this study as resistance was reported for extended spectrum β-lactamase and other novel carbapenemase resistance.…”
Section: Discussionmentioning
confidence: 76%
“…These variance reports might be associated with the region or environmental activities in their individual isolation sites or the flexible and changing nature of V. cholerae in diverse environment [ 64 ]. In the reports of Guevara et al [ 65 ], resistance was not observed amongst the Vibrio strains but the trend changed over time as subsequent simultaneous report between 1992 and 2017 shows that [ 59 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] V. cholerae is emerging in resistant profile and multiple antibiotic resistance which have also extended from penicillanases or β-lactamases of various class to carbapenemases as affirmed during their study. This is further affirmed in this study as resistance was reported for extended spectrum β-lactamase and other novel carbapenemase resistance.…”
Section: Discussionmentioning
confidence: 76%
“…In South America, Dabanch et al . () reported the first case of septicaemia due to V. parahaemolyticus in Puerto Montt, in Chile, which occurred in 2008.…”
Section: Vibrio Parahaemolyticus Occurrence In South Americamentioning
confidence: 99%
“…Essa infecção é causada por uma bactéria entérica que normalmente vive na costa do Oceano Pacífico, especialmente na costa do Japão, do Chile, da Nova Zelândia, do Canadá, da Austrália e dos Estados Unidos, produzindo uma enterite autolimitada com duração de 3 dias, que resulta em vômito e diarreia 42,43 . Essa infecção é adquirida pela ingestão de frutos do mar crus ou mal cozidos, ou devido à contaminação cruzada.…”
Section: Alimentosunclassified